Emerging Adults Thinking About Their Future: Development of the Portuguese Version of the Hopes and Fears Questionnaire. Issue 6 (December 2019) - Fonseca, Gabriela; Silva, José Tomás da; Paixão, Maria Paula; Cunha, Diana; Crespo, Carla; Relvas, Ana Paula
Nowadays, emerging adults live in a context of macroeconomic uncertainty. As the major processes of one's identity exploration currently occur in emerging adulthood, understanding how these individuals foresee their future is of special interest. The purpose of this study was 2-fold: (i) to investigate future orientation (FO) in a sample of Portuguese emerging adults and (ii) to validate the Portuguese version of the Hopes and Fears Questionnaire. Data from 332 individuals were analyzed. Results demonstrated that participants' future hopes and fears were mainly pertaining to education, work/career, and family/marriage. Participants also reported concerns related to their financial resources. Thus, the results showed that participants' FO reflected major tasks associated with their development stage, as well as contextual factors, such as macroeconomic trends. This study contributed to the knowledge of emerging adulthood in Portugal, simultaneously providing a useful and reliable measure to evaluate emerging adults' FO in that country.